KEPEMIMPINAN TRANSFORMASIONAL DI SEKOLAH DIGITAL: INOVASI ATAU ANCAMAN TERHADAP NILAI-NILAI TRADISIONAL? - Abdul Hamid (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the dynamics of transformational leadership in digital schools, focusing on the tension between the innovations offered and the potential threats to traditional values ​​in education. The background of this study is the shift in the educational paradigm due to massive digitalization, which requires principals to adapt to a more flexible, visionary, and technology-based leadership model. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews with principals, teachers, and education personnel in five digital schools in large cities and semi-urban areas. The results of the study show that transformational leadership encourages the creation of technology-based learning innovations, increased teacher participation, and accelerated decision-making. However, resistance also emerged from some senior teachers who felt that values ​​such as conventional discipline, etiquette, and social hierarchy were starting to be marginalized. This study contributes to the literature on educational leadership by showing that the success of transformational leadership in digital schools is highly dependent on the leader's ability to maintain a balance between technology adoption and the preservation of deep-rooted educational values. These findings can be a reference for policy makers and education practitioners in designing adaptive and sustainable leadership strategies in the digital era.